PUlmonotoxicyty Of syNThETIC POLYMERS combustion products - D. V. Trishkin; S. V. Chepur; P. G. Tolkach; V. A. Basharin; O. V. Chubar; A. S. Gogolevskiy; M. A. Tyunin; E. G. Kruchinin; R. O. Vasilev; E. A. Tarasov (Сибирский научный медицинский журнал, 2019)
Pulmonotoxicants are the substances causing structural and functional disorders of respiratory system. The main sources of pulmonotoxicants in the environment are thermal decomposition of synthetic polymeric materials in fires. The possibility of formation of pulmonotoxicants during the combustion of synthetic polymers of different composition with regard to the conditions of combustion (temperature, time, sufficient oxygen) was analyzed. The risk of lung damage has been considered taking into account the duration of exposure to the toxicant. In addition to general toxic carbon monoxide and cyanide, the products of thermal destruction of halogen-containing and nitrogen-containing substances pose a great danger in case of fire due to their high pulmonotoxicity. The lung damage risk is considered with account for toxicants exposure duration. The pulmonotoxicants classification has been proposed according to their hazard in relation to their concentration in the air. Main mechanisms of effect of pulmonotoxicants formed during the pyrolysis of various polymeric synthetic materials have been proposed. The description of clinical manifestations as the result of intoxication with these materials under various toxodoses effect has been shown. The hazardous risk spectrum has changed depending on the toxic exposure duration that determines the variance of treatment approaches: from possible etiotropic treatment to pathogenetic therapy of toxic pulmonary edema.